Introduction : Sound symbolism in the age of digital orality. A perspective on language beyond 'nature' and 'culture' (Signifiances (Signifying), 2020)
After recalling the main empirical evidence in favour of sound symbolism, this Introduction presents the contributions offered by the authors of this issue of Signifiances (Signifying). It then addresses some of the epistemological and metaphysical issues that a full integration of sound symbolism into language theory entails, particularly concerning the relationship between language and reality, and between nature and culture. Finally, it proposes to explain the centuries-old preference of scholars for the arbitrariness of the sign as an effect of the pre-eminent role that writing on paper has played in their pragmatic-cognitive experience of language up to the digital revolution.